Cross-segmental parties in consociational systems: Downplaying prowess to access power in Northern Ireland. (November 2022) - Agarin, Timofey; Jarrett, Henry
Political parties are afforded a key role in making consociational democracy work; however, parties that dis-identify with salient identities and appeal to voters across the ethno-political divide face barriers when interacting with voters and with other, segmental parties. Nevertheless, such cross-segmental parties often thrive and even ascend to power. Northern Ireland's cross-segmental parties – the Alliance Party, the Green Party, and People before Profit – have sought to traverse group-specific voter interests and set their agenda apart from that of segmental parties. For such parties to be considered 'coalitionable', they should outline their (potential) governing contribution to complement other political parties' agendas. Cross-segmental parties' participation in government makes them appear electable, but it is the focus on bipartisan concerns that consolidates their electoral success and ensures their political relevance. We focus on the evolution of Alliance's political agenda and fill a gap in the literature on the relevance of cross-segmental parties in consociations.